Analisis Penentuan margin pada produk pembiayaan murabahah di BMT Madani Sepanjang - Pratama, Trias Devi; Suryaningsih, Sri Abidah (Jurnal Ekonomika dan Bisnis Islam, 2019)
This study uses a descriptive qualitative approach to determine the determination of margins on Murabahah financing at BMT Madani Sepanjang. The type of data used by the author are primary and secondary data. Primary data comes from interviews with BMT and secondary data derived from data on the number of members of 2016-2018, DSN-MUI fatwa and previous research. Data collection techniques in this study used interviews, observation and documentation. The results of this study indicate that BMT Madani As long as it sets the selling price on murabahah products using a proportional method or flat method in accordance with DSN-MUI Fatwa No. 84 / DSN-MUI / XII / 2012. The BMT margin is around 1% -1.6% and has its own sharia standard, namely the credit committee.